Mentoring as strategy for teaching improvement in universities, a systematic review - López-Aguado, Mercedes; Scialdone, Onofrio (Revista Complutense de Educación, 2026)
This paper presents the results of the systematic review on the role of peer mentoring in improving university teaching. The review was conducted following the PRISMA 2020 guidelines, in its updated version of 2020, have been followed. Following these guidelines, the research questions are organized into three main categories: bibliographic characteristics of the documents, methodological strategies employed, and a detailed description of mentoring procedures. Subsequently, the eligibility criteria, information sources, search terms, and the filtering and selection procedures are outlined. The methodological section concludes with a description of the process used to code and synthesize the information. The analysis and results of the review follow the structure and logic of the research questions, being presented in the three previously mentioned sections and answering each question individually. The main findings highlight the limited number of publications and the tendency for these experiences to align with traditional mentoring models. These models are typically focused on training novice faculty, guided by senior mentors, within the framework of professional development processes with formally established procedures. These findings are discussed in relation to more contemporary models, which establish networked support relationships (both formal and informal) among faculty members with varying levels of experience and areas of expertise.